The Impact of Economic Freedom and International Tourism on International Trade: An Empirical Study in Asian Countries - Dang, Buu Kiem (Organizations and Markets in Emerging Economies, 2024)
The objective of this study is to analyze the impact of economic freedom and the development of international tourism on international trade, encompassing exports, imports, and total trade. The research sample includes 22 Asian countries over the period from 1995 to 2020. The study employs the System Generalized Method of Moments (GMM) for estimating the research models. Results indicate that economic freedom, business freedom, and trade freedom play a crucial role in international trade activities (both exports and imports). Furthermore, the development of international tourism also demonstrates a significantly positive impact on trade (both exports and imports). The study suggests that policies towards economic openness, increasing economic freedom, business freedom, and trade freedom should be carefully considered and promoted within the trade development strategies of nations. Additionally, economic policies should also focus on solutions to attract international tourists not only as a source of foreign currency but also as a support to foster the development of trade.